Phenomenological investigation of negative attitudes towards marriage in female students - Fariba Tabkhi; Marieh Dehghan Manshadi; Yasser Rezapour-Mirsaleh (BMC Psychology)
Abstract Marriage, as a social institution, has evolved over time and is now often associated with delays in marriage age and the development of negative attitudes. These negative attitudes, which encompass factors such as fear, anxiety, social pressure, and doubts about marriage, are particularly prevalent among female students. Investigating these negative attitudes, particularly among female students, through qualitative and phenomenological methods, offers valuable insights into the factors shaping these perspectives. Therefore, this study aimed to explore the phenomenology of negative attitudes towards marriage among female students at the Islamic Azad University, Yazd branch, in the context of Iranian cultural and social influences. This research employed a qualitative phenomenological approach. Among the unmarried female students of the Islamic Azad University, Yazd branch, in the academic years 2023–2024, those who scored low on the Attitude towards Marriage Scale (J Divorce Remarriage 29:83–91, 1998) were selected for semi-structured interviews. Data collection continued until saturation was reached. Ultimately, 12 students were purposefully selected and interviewed based on specific inclusion, and exclusion criteria. The data were analyzed using an interpretive analysis method. The analysis identified four main themes, ten sub-themes, and fifty-five semantic units. The main themes and their sub-themes were: (1) Interpersonal factors (negative emotions about the future, feelings of inadequacy for forming a marital life, lack of preparedness for marital challenges, idealism, and a sense of not needing marriage); (2) Family factors (family idealism and generational differences); (3) Social factors (imitating others' lives and mistrust in others’ support); and (4) Economic factors (financial concerns). The results indicate that negative attitudes towards marriage among female students are influenced by interpersonal, family, social, and economic factors. These factors, whether directly or indirectly, contribute to doubts and delays in marriage decisions, significantly shaping negative views on the formation of marital life. Therefore, educational and counseling programs focused on enhancing life skills, adjusting attitudes, and reducing idealism among female students may facilitate the decision-making process regarding marriage.